Cycling and sustainability - Parkin, John, 1946- (Bingley : Emerald, 2012)
This title explores the reasons for difficulties in making cycling mainstream in many cultures, despite its claims for being one of the most sustainable forms of transport.
Keywords: Bicycle commuting; Bicycle lanes; Cycling -- Social aspects